Репрезентація обставинної семантики формою прислівника в романі П. Загребельного «Дума про невмирущого» - Юрченко, Ніна; Yrchenko, Nina (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті йдеться про репрезентацію обставинної семантики формою прислівника в романі Павла Загребельного «Дума про невмирущого». Підкреслено, що специфіку прислівника як частини мови похідного типу відображають обставинні прислівники, які репрезентують семантику відношень, не властиву іншим частинам мови. Пояснено, що обставинні прислівники утворилися в інший спосіб, ніж означальні. Ці мовні одиниці належать до колишніх відмінкових або прийменниково-відмінкових форм деяких іменників чи дієслів.У статті проаналізовані також прислівники неморфологізованого типу. Схарактеризовані прислівники місця, часу, причини, мети та допустовості. Наведено приклади займенникових прислівників, що мають спільну з власне-прислівниками категорійну семантику. The article deals with representation of the adverbial semantics through the form of the adverb in the novel by «Duma about the immortal man». Form of the adverb morphologically realizes adverbial relations are noted. This is explained by the fact that, adverb forms is formed and continue to create through the using of the forms such type. The adverbial adverbs reflect the specificity of adverbs as parts of speech derived type, because they represent a semantic relationship, which is not characteristic of other parts of speech are underlined. The adverbial adverbs formed by other means than another type of the adverbs do this is explained. The such adverbs belong to the case forms or the prepositional-case forms of some nouns and verbs. The meanings of the non-morphologyzed are analyzed in the article too. The adverbs of the place, time, purpose and concessions are characterized. The examples of pronominal adverbs, which have common categorical semantics with other adverbs words is given in this article.
Representation of the adverbial semantics through the form of the adverb in the novel by «Duma about the immortal man»
Keywords: обставина; прислівник; адвербіалізація; обставинні прислівники; групи прислівників за значенням; adverb; adverbial modifier; adverbialization; adverbial adverbs; types of the meaning of the adverbs